The Relationship between Anxiety Levels and Academic Achievement among Students in Selected Secondary Schools in Lang’ata District, Kenya - Syokwaa, Kaula assumpta; Aloka, Peter, J. O.; Ndunge, Ndeke Florentina (MCSER Publishing, Rome-Italy, 2014)
The study investigated the relationship between anxiety levels and academic achievement among students in selected secondary schools in Lang’ata district, Kenya. The study adopted an ex-post facto design and the sample size comprised 180 secondary school students (90 boys and 90 girls). A personality anxiety self-examination quiz and an anxiety test examinations were administered to participants. Data was analyzed by using both descriptive and inferential statistics. The results showed a presence of high personality anxiety levels at 79%, while the test anxiety indicated a relatively low-normal anxiety level of 27%. The study found out that, there was a correlation between anxiety levels and academic achievement, and that high anxiety levels had a negative impact on the quality of academic results recorded by students. The study also established that students’ encountered some high anxiety causing challenges which affect their ability to perform effectively, and girls were found to be more prone to high anxiety levels as compared to boys. The study recommended that, students should take responsibility to seek for anxiety management help from teacher counselors, other teachers. DOI: 10.5901/jesr.2014.v4n3p403
Keywords: relationship; anxiety level; academic achievement; secondary school; students.